Paleobiology of a large mammal community from the late Pleistocene of Sonora, Mexico. (July 2021) - Short, Rachel A.; Emmert, Laura G.; Famoso, Nicholas A.; Martin, Jeff M.; Mead, Jim I.; Swift, Sandy L.; Baez, Arturo
Abstract: A paleontological deposit near San Clemente de Térapa represents one of the very few Rancholabrean North American Land Mammal Age sites within Sonora, Mexico. During that time, grasslands were common, and the climate included cooler and drier summers and wetter winters than currently experienced in northern Mexico. Here, we demonstrate restructuring in the mammalian community associated with environmental change over the past 40, 000 years at Térapa. The fossil community has a similar number of carnivores and herbivores whereas the modern community consists mostly of carnivores. There was also a 97% decrease in mean body size (from 289 kg to 9 kg) because of the loss of megafauna. We further provide an updated review of ungulates and carnivores, recognizing two distinct morphotypes of Equus, including E . scotti and a slighter species; as well as Platygonus compressus ; Camelops hesternus ; Canis dirus ; and Lynx rufus; and the first regional records of Palaeolama mirifica, Procyon lotor, and Smilodon cf. S . fatalis . The Térapa mammals presented here provide a more comprehensive understanding of the faunal community restructuring that occurred in northern Mexico from the late Pleistocene to present day, indicating further potential biodiversity loss with continued warming and drying of the region.